A Survey on Data Recovery Approaches in Cloud Computing Environment - Benjamin Franklin, I; Ravi, TN (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing system provides a lot of convenient computational and data storage services to the users. Data transfer to the cloud environment is convenient. The cloud computing system generates a large amount of private data on the main cloud. Then, the need of data recovery services are increasing day-by-day and require development of efficient data recovery technique. The aim of the data recovery technique is to collect the information from the backup server, when the server lost the data and unable to provide the data to the user. Various techniques are proposed for efficient recovery of data. This paper focuses on the comprehensive review of the data recovery approaches, issues in data recovery, failures in cloud storage, key factors and their role in data recovery and existing data security technologies in the cloud. The main objective of the review paper is to summarize the prevailing data recovery techniques in the cloud computing domain.